2015
DOI: 10.3791/52375
|View full text |Cite
|
Sign up to set email alerts
|

A Surgical Procedure for Resecting the Mouse Rib: A Model for Large-Scale Long Bone Repair

Abstract: This protocol introduces researchers to a new model for large-scale bone repair utilizing the mouse rib. The procedure details the following: preparation of the animal for surgery, opening the thoracic body wall, exposing the desired rib from the surrounding intercostal muscles, excising the desired section of rib without inducing a pneumothorax, and closing the incisions. Compared to the bones of the appendicular skeleton, the ribs are highly accessible. In addition, no internal or external fixator is necessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…Like appendicular long bones, the bony portion of the rib develops via an endochondral process including growth plates at either end and a central hollow bone marrow cavity. Both human and murine rib bones display remarkable regenerative potential (Srour et al, 2015; Tripuraneni et al, 2015), however the cellular basis for such large-scale repair remains unknown. To better understand the cellular sequence of events during regeneration, we analyzed 3 mm rib bone defects at sequential time points up to 10 weeks post-resection (wpr) (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Like appendicular long bones, the bony portion of the rib develops via an endochondral process including growth plates at either end and a central hollow bone marrow cavity. Both human and murine rib bones display remarkable regenerative potential (Srour et al, 2015; Tripuraneni et al, 2015), however the cellular basis for such large-scale repair remains unknown. To better understand the cellular sequence of events during regeneration, we analyzed 3 mm rib bone defects at sequential time points up to 10 weeks post-resection (wpr) (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…We next examined the source of the skeletal cells that mediate repair. These cells are likely derived from the periosteum, since removal of the periosteum along with the bone, results in a failure of cartilage callus formation (Figure 2—figure supplement 1) and subsequent bone repair (Tripuraneni et al, 2015). Sox9 is a master regulatory gene of chondrogenesis, and a previous study indicated that Sox9+ cells in the femur periosteum can contribute to callus formation after fracture (He et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations